Beyond vertebrates: Drosophila melanogaster as a model to study negative symptoms of schizophrenia - Elgueta-Reyes, Maximiliano; Hidalgo, Sergio; Campusano, Jorge M. (Frontiers in Psychiatry, 2025)
Schizophrenia is a complex neuropsychiatric disorder characterized by positive, negative, and cognitive symptoms. While positive symptoms have been extensively studied, negative symptoms—such as anhedonia, social withdrawal, and apathy—remain challenging to model and treat. Vertebrate animal models for schizophrenia have provided insights into some of the underlying mechanisms associated with this disorder. Recently, Drosophila melanogaster has emerged as a valuable model due to its genetic tractability, conserved neurochemical pathways as compared to vertebrates, and suitability for high-throughput behavioral analyses. Mutations in genes such as dysb1, Rim, and Neuroligins have been linked to behaviors in flies resembling negative symptoms of schizophrenia, supporting the relevance of this animal model in psychiatric research. Moreover, behavioral paradigms aimed at assessing social interaction, motivation, and anhedonia in Drosophila are being refined to better capture schizophrenia-related deficits. The use of Drosophila enables precise investigation of neural circuits and molecular pathways underlying negative symptoms of schizophrenia, research that has the potential to lead to novel therapeutic targets.